2010
DOI: 10.3819/ccbr.2010.50007
|View full text |Cite
|
Sign up to set email alerts
|

Picture Perception in Birds: Perspective from Primatologists.

Abstract: In their target article, Weisman and Spetch (2010) question the validity of pictures to present real things to birds, mostly because pictures are primarily made for the human eye, and not for the eye of birds with different functional properties. Here, we argue that this issue of picture validity is similarly critical for primatologists, even when they study the "higher" nonhuman primates with a more similar visual system, and emphasize cognitive limitations in referential abilities that may be an important so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In our experiment, we showed that horses were also capable of the opposite process: transferring 3-dimensional information (real people) to 2-dimensional information (photographs). It is not apparent that animals would have this ability 13 because photographs represent only a small part of the information concerning reality: no recognition is possible through odors, behavior or voice, for example, and there is also a loss of visual information such as depth, perspective or movement 14 . Thus, some species, such as dogs, have difficulties recognizing photographs of faces and particularly when only the central part is visible 12 , whereas they are quite capable of recognizing faces in real life conditions 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, we showed that horses were also capable of the opposite process: transferring 3-dimensional information (real people) to 2-dimensional information (photographs). It is not apparent that animals would have this ability 13 because photographs represent only a small part of the information concerning reality: no recognition is possible through odors, behavior or voice, for example, and there is also a loss of visual information such as depth, perspective or movement 14 . Thus, some species, such as dogs, have difficulties recognizing photographs of faces and particularly when only the central part is visible 12 , whereas they are quite capable of recognizing faces in real life conditions 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the latter is that it excludes any risk of interference from other sensory information, particularly olfactory cues. However, using photographs can be particularly complex for non-human species 13 . Indeed, the animal must understand that a relationship exists between the real individual and his/her 2-dimentional image seen in a photograph.…”
mentioning
confidence: 99%
“…Therefore understanding the visual system of the species under investigation can help with finding the most appropriate stimuli to present, and the ones that are most likely to reveal abilities that do exist. Fagot and Parron (2010) also argue that the field is in need of a clear framework for describing differences in picture processing, and they suggest that the framework include a distinction between "independence", "confusion" and "equivalence" modes of processing pictures. I agree that a framework is needed and that these distinctions are important.…”
Section: Picture Processing Is Not Just Perceptualmentioning
confidence: 97%
“…The commentary by Fagot and Parron (2010) raises the excellent point that a failure to perceive correspondence between pictures and their referents can arise from more than just perceptual limitations. They convincingly argue, based on research with non-human primates, that presentation of stimuli that are perceptually appropriate to the species is not a sufficient condition for correspondence.…”
Section: Picture Processing Is Not Just Perceptualmentioning
confidence: 97%
“…But this should not be taken to mean they are always correct in their opinions. I highly recommend two of the commentaries (see Fagot & Parron, 2010;Jitsumori, 2010): these provide valuable perspectives on cognitive and perceptual acts that are important to categorization (see Spetch, 2010).…”
mentioning
confidence: 98%